Analyzing slow drying in a porous medium placed adjacent to laminar airflow using a pore-network model. (1st December 2016) - Xu, Zhenyu; Pillai, Krishna M.
ABSTRACT: A novel unified implicit computational framework and a unique pore-to-cell meshing method is used to predict, by coupling the inside-drying outside-flow processes, the slow drying of a pore-network-represented porous medium placed adjacent to a laminar flow of air in a slit. The effects of numerical algorithms, spatial and temporal discretization schemes, and meshing methods in minimizing computational effort are studied. The numerical solutions of the outer and inner processes are tested against several benchmark studies. The external air velocity affects drying during the initial stages. The microstructure of the pore network (P-N is found to have a strong influence on drying.